Indoor Air Pollution, Sorbent Selection, and Analytical Techniques for Volatile Organic Compounds - Jaganathan Senthilnathan; Ki-Hyun Kim; Jo-Chun Kim; Jin-Hong Lee; Hee Nam Song (Asian Journal of Atmospheric Environment, 2018)
Indoor air quality has received wide spread attention due to the recognition of the presence of diverse toxic volatile organic compounds (VOCs) and their harmful impacts on human health. This review discusses the chemicals in indoor air and their sources and associated chemical (primary/secondary) reactions. The merits and demerits of commercially available adsorbents and synthetically prepared carbon/non-carbon-based adsorbents for indoor air sampling are discussed. Also, important parameters (like breakthrough volume, specific adsorption capacity, reaction mechanism, and desorption efficiency) are evaluated. The recent advancements in analytical techniques and insight into the complexity involved in air sampling are emphasized. The application of commercially available adsorbents and synthetically prepared carbon/non-carbon-based adsorbents for indoor air sample collection are discussed.